Intracellular localization of vitellogenin receptor mRNA and protein during oogenesis of a parthenogenetic tick, Haemaphysalis longicornis - Rika Umemiya-Shirafuji (Parasites & Vectors, 2019)
Abstract Background Vitellogenin (Vg), a key molecule for oocyte development synthesized in the fat body during blood-feeding, is released into the hemolymph and then taken into the oocytes via Vg receptor (VgR) in ticks. Previously, we showed that VgR mRNA is expressed in the ovary at the adult stage of parthenogenetic Haemaphysalis longicornis ticks and its expression increases after blood-feeding. However, intracellular localization of VgR mRNA and protein at each developmental stage of oocytes during oogenesis remains largely unclear. Methods mRNA and protein expression profiles of H. longicornis VgR (HlVgR) in the oocytes from the unfed to oviposition periods were analyzed by real-time PCR, in situ hybridization, and immunostaining. To elucidate the timing of the onset of Vg uptake, RNA interference (RNAi)-mediated gene silencing of HlVgR was performed. Results In situ hybridization revealed that HlVgR mRNA was detected in the cytoplasm of stage I-III oocytes, and weaker positive signals for HlVgR mRNA were found in the cell periphery of stage IV and V oocytes. Likewise, HlVgR protein was detected by immunostaining in the cytoplasm of stage I-III oocytes and in the cell periphery of stage IV and V oocytes. Each developmental stage of the oocytes showed distinct patterns of mRNA and protein expression of HlVgR. Moreover, RNAi of HlVgR caused delayed or arrested development in the oocytes. The ovaries of control ticks showed all developmental stages of oocytes, whereas stage I-III oocytes were found in the ovaries of HlVgR-RNAi ticks at 5 days after engorgement. Conclusions These results suggest that active uptake of Vg is required for development from stage III to stage IV during oogenesis. Our data clearly revealed an apparent shift in the intracellular localization of VgR for both mRNA and protein level in oocytes during oogenesis.